Evaluation of carbon monoxide emissions of electric power generators used in buildings in Ibadan Metropolis, Nigeria - Akeem Bolaji Wahab (Economic and Environmental Studies (E&ES), 2019)
Poor supply of electricity to different settlements over the years in Nigeria has forced building occupants to shift to dependence on generators. This study thus determined outdoor and indoor carbon monoxide levels of generators used in both residential and commercial buildings and assessed its impact on the users and the environment. The study was carried out in Ibadan Metropolis, Nigeria, which was divided into core, transition and suburban zone respectively. Five (5) residential and commercial buildings respectively were purposively selected in each of the zones of the study area. The HT- 1000 digital LCD carbon monoxide meter was used to take measurements of the emissions of carbon monoxide with conformity to NESREA AND OSHA standards. The outdoor emission levels of the carbon monoxide before or during the use of generators were taken at 0, 2 and 4 m respectively from the external walls of the buildings sampled and the corresponding indoor measurements were taken internally at 1.2-1.5m above floor area. The data collected were analysed with the use of statistical methods such as t-test, trend analysis and Kolmogorov smirnov test. The results showed that outdoor and indoor measurements of carbon monoxide emissions levels were highest in buildings in the core zone either before or during the use of generating sets. Reduced carbon monoxide levels during use of generators were obtained at distance limits beyond 2 m from external walls of buildings across zones of the study area. In view of the measurements taken, being above limits set by statutory bodies, during use of generators, and its attendant effects on the environment and building occupants, it was recommended that its users should be enforced to position them in enclosures located away from external walls of buildings and government should license only sales of generating sets with emission control mechanisms.
Keywords: Q41; Q53; 330; environment; electricity; buildings; generators; carbon monoxide emissions; impacts